Microscale coiling in bis-imidazolium supramolecular hydrogel fibres induced by release of a cationic serine protease inhibitor - Limón, David; Jiménez-Newman, Claire; Calpena, Ana C.; Gonzalez-Campo, Arántzazu; Amabilino, David A.; Pérez-García, Lluïsa (Royal Society of Chemistry, 2017)
Gels formed by a gemini dicationic amphiphile incorporate a serine protease inhibitor, which could be used in a new approach to the treatment of Rosacea, within the fibres as well as in the space between them, affecting a number of gel properties but most importantly inducing remarkable fibre coiling at the microscopic level as a result of drug release from the gel. Drug release and skin permeation experiments show its potential for topical administration.